The "tragic mulatta" revisited : race and nationalism in nineteenth-century antislavery fiction - Raimon, Eve Allegra, 1957- (New Brunswick, N.J. : Rutgers University Press, 2004)
Annotation Since its inception, the United States has been intensely preoccupied with interracialism. The concept is embedded everywhere in our social and political fabric, including our sense of national identity. And yet, in both its quantitative and symbolic forms, interracialism remains an extremely elusive phenomenon, causing policy makers and census boards to wrangle over how to delineate it and, on an emblematic level, stirring intense emotions from fear to fascination. In The "Tragic Mulatta" Revisited, Eve Allegra Raimon focuses on the mixed-race female slave in literature, arguing that this figure became a symbolic vehicle for explorations of race and nation-both of which were in crisis in the mid-nineteenth century. At this time, judicial, statutory, social, and scientific debates about the meaning of racial difference (and intermixture) coincided with disputes over frontier expansion, which were never merely about land acquisition but also literally about the "complexion" of that frontier. Embodying both northern and southern ideologies, the "amalgamated" mulatta, the author argues, can be viewed as quintessentially American, a precursor to contemporary motifs of "hybrid" and "mestizo" identities. Where others have focused on the gendered and racially abject position of the "tragic mulatta," Raimon reconsiders texts by such central antislavery writers as Lydia Maria Child, William Wells Brown, Harriet Beecher Stowe, and Harriet Wilson to suggest that the figure is more usefully examined as a way of understanding the volatile and shifting interface of race and national identity in the antebellum period
Introduction : reading miscegenation -- 1. Of romances and republics in Lydia Maria Child's miscegenation fiction -- 2. Revising the "quadroon narrative" in William Wells Brown's Clotel -- 3. Resistant Cassys in Richard Hildreth's The slave and Harriet Beecher Stowe's Uncle Tom's cabin -- 4. Public poor relief and national belonging in Harriet Wilson's Our nig -- Coda : the "tragic mulatta" then and now.
Includes bibliographical references (pages 159-189) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: American fiction -- 19th century -- History and criticism; Race in literature; Nationalism and literature -- United States -- History -- 19th century; African American women in literature; Antislavery movements in literature; Multiracial people in literature; Tragic, The, in literature; Nationalism in literature; Slavery in literature; Women in literature; Roman américain -- 19e siècle -- Histoire et critique; Race dans la littérature.; Nationalisme et littérature -- États-Unis -- Histoire -- 19e siècle.; Noires américaines dans la littérature.; Mouvements antiesclavagistes dans la littérature.; Métis dans la littérature [Annulée]; Tragique dans la littérature.; Nationalisme dans la littérature.; Esclavage dans la littérature.; Femmes dans la littérature.; LITERARY CRITICISM -- American -- General; African American women in literature; American fiction; Antislavery movements in literature; Nationalism and literature; Nationalism in literature; Race in literature; Multiracial people in literature; Slavery in literature; Tragic, The, in literature; Women in literature; United States; Nationalbewusstsein; Literatur; Sklaverei; Rassenfrage; USA; 1800-1899; Criticism, interpretation, etc; History